Kebijakan Pembangunan Nasional: dari Pertumbuhan (Growth) Menuju Kebahagiaan (Happiness) - Wibowo, Muhammad Ghafur (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
This study aims to demonstrate the reorientation toward the national  development  policy  of  quantitative  macro  size  (growth) towards  a  more  qualitative  measure  (happiness).  The  test  results  of multiple  linear  regression  on  the  variable  value  of  public  happiness index  in  each  province  of  Indonesia  with  variable  poverty, income inequality  and  income  per  capita  shows  quite  interesting  results. Apparently, only the poverty variable has significant negative effect on the  happiness  index.  This  means  that  poor  people  in  Indonesia  who have  limitations  in  various  aspects  of  life  feel  the  lowest  levels  of happiness. Another interesting finding is that income and the income gap does not significantly influence the level of happiness of society. Therefore,  the  government  needs  to  pay  more  attention  to  various aspects  such  as  the  quality  of  family  life,  social  and  various  other aspects.